Engineered Protein Nanocages for Targeted and Enhanced Dermal Melanocyte Cellular Uptake. Issue 7 (5th May 2021) - Bhaskar, Sathyamoorthy; Thng, Steven; Lim, Sierin
Abstract : Hyperpigmentation is a major cosmetic concern that results from the overproduction of melanin from melanocyte cells in the skin. Current formulations of therapeutic drugs and active molecules that are intended to be delivered to the melanocytes are not targeted, leading to inefficient delivery and undesirable side effects. There is a compelling need for delivery vehicles that target melanocytes to effectively regulate melanin production. Self‐assembling protein nanocages (PNCs) have been shown to offer safe and efficient delivery of active molecules. They are versatile protein nanoparticle platforms that can be engineered to display functional ligands to impart specific biological functions. In this work, E2 PNCs are engineered to display alpha‐melanocyte‐stimulating hormone (AlphaMSH) peptides as ligands for targeting and enhancing uptake by melanocytes. At 500 pM, the AlphaMSH‐modified E2 PNCs show 4‐fold increase in melanocyte cell uptake compared to bare E2 PNCs in 2 hours. This increase was less pronounced in keratinocytes. Competitive inhibition assay proves that the MC1R melanocyte cell surface receptor facilitates the uptake of E2 PNCs by mediating interaction with the displayed AlphaMSH peptides. PNCs can thus be used as targeted delivery vehicles of drugs and active molecules to melanocytes for the management of hyperpigmentation. Abstract : Melanocytes are the primary cells involved in skin hyperpigmentation. E2 protein nanocages (PNCs) are engineered to display AlphaMSH targeting ligand for homing to the MC1R receptors on melanocytes. AlphaMSH ligand modification enhances the cellular uptake of the PNCs by 4 folds in melanocytes compared to insignificant change in keratinocytes. PNC is shown to be a versatile platform for cutaneous delivery.